Innovations in Fuel Economy and Sustainable Road Transport : 8-9 November 2011, Pune, India (Woodhead Publishing, 2011)
This book presents the papers from the Innovations in Fuel Economy and Sustainable Road Transport conference, held in Pune, India, 8-9 November, 2011. Papers examine advances in powertrain, alternative fuels, lightweight vehicles, electric vehicles and hybrid vehicles. An international assembly of senior industry representatives provide insight into research and technological advances in low carbon technology sustainability for road transport, helping towards achieving stringent emissions standards and continual improvements in fuel economy efficiency, all in an expanding Indian market. These technical papers from industry and academia discuss the developments and research of leading organisations.